(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Interleukin-8/CXCL 8 (IL-8) is a potent chemokine, angiogenic factor, autocrine growth factor with direct growth-promoting effect on many human cancers, and overexpression of IL-8 in carcinomas allows tumor growth and invasion. Ribonucleic acid (RNA) interference is an effective post-transcriptional gene silencing concept, specifically identifying and down-regulating the target gene’s expression. Small interfering RNAs (siRNAs) acts as a promising and powerful tool for application in gene therapy. However, siRNA therapies have been impeded by a lack of potential delivery systems. In this scenario, carbon nanotubes are used as an emerging platform for constructing safe, specific, and effective siRNA delivery systems. In this present work, the gene expression of IL-8 was studied in A 549 and H 460 non-small cell lung cancer cells using reverse transcription polymerase chain reaction (RT-PCR), and enzyme-linked immune sorbent assay produced significant levels of IL 8 protein (9.57 ± 1.6 ng mL-1 per 106cells and 83.26 ± 2.8 ng mL-1 per 106cells). Then potential tumor targeting nano delivery system was designed using single-walled carbon nanotubes (SWNTs), non-covalently functionalized with DSPE-PEG 2000 amine polymer to improve the solubility biocompatibility and lower the cytotoxicity. Then these functionalized SWNTs were conjugated to IL 8 siRNA via cleavable disulfide bond using a Sulfo-LC-SPDP cross-linker. The optimized formulation with enhanced biocompatibility and solubility may effectively be used as a nanocarrier for the potential delivery of IL 8 siRNA to tumor target sites.